Retrospective Analysis of Acute Hepatitis B Virus Infections and Chronicity Rates - Sevil ALKAN ÇEVİKER (Flora Infeksiyon Hastalıkları ve Klinik Mikrobiyoloji Dergisi, 2020)
Introduction: The aim of this study was to analyze the clinical and laboratory features and the chronicity rates of hepatitis B in adult acute hepatitis B virus (HBV) patients.